MACHINE LEARNING BASED PADDY DISEASE PREDICTION AND CLASSIFICATION USING CONVOLUTIONAL NEURAL NETWORK - Mr. R. Venkadesh, M.E.; Srimalini S; Amirtha Dharshini G; Sujeetha JR (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The essential wellspring of nourishment for everybody is horticulture. Broad review shows that farming is essentially affected by the advancement of ailments in rice fields. Ranchers are confronted with the difficult undertaking of unequivocally distinguishing contamination in their corn crops during the foliar illness stage. Hence, to foresee illnesses, programmed sickness discovery calculations should focus more on early signs of paddy infections. The sorts of harvests that can be developed and their yields are fundamentally affected by these sicknesses, which first assault the leaves prior to spreading all through the whole rice field. Subsequently, to successfully control the spread of disease and backing solid plant development, exact classification and early distinguishing proof of paddy sicknesses are fundamental. This article proposes a convolutional neural network (CNN) model for paddy sickness order with an end goal to defeat these hardships. The proposed approach searches for sores on the leaves that could be the consequence of an illness utilizing picture handling calculations. Through preprocessing, CNN’s component testing precision with classifier is better than that of other current models. Utilizing genuine Inaba photographs, the viability of the proposed consideration-based preprocessing was additionally affirmed. The CNN model has a higher characterization exactness when contrasted with other exchange learning calculations.